Epithet in the Boof-e koor-e Sadeq Hedayat - Hamid Khanian (مطالعات زبانی و بلاغی)
Epithet is a literary technique used in poetry and prose to express artistic meanings and concepts and to express emotions and feelings. Hedayat is one of the authors and founders of modern Persian fiction who has used this literary technique in his works, especially Blind Owl. In this article, this technique has been studied in a descriptive-analytical way, in order to show one of the beauties of this work, to determine its artistic ability and the beautiful taste of its author. The results show that most of the epithet used in Blind Owl are compound and simple, epithet which are in the form of similes, metaphors, ironies , personification, bombast, and conglobatio, and the highest frequency belongs to the personification epithet and the lowest belongs to metaphor.